Digital diagnostic support in rheumatology Digitale Diagnoseunterstützung in der Rheumatologie - Knitza, Johannes; Krusche, M.; Leipe, J. (Zeitschrift für Rheumatologie, 2021)
Only the correct diagnosis enables an effective treatment of rheumatic diseases. Digitalization has already significantly accelerated and simplified our everyday life. An increasing number of digital options are available to patients and medical personnel in rheumatology to accelerate and improve the diagnosis. This work gives an overview of current developments and tools for patients and rheumatologists, regarding digital diagnostic support in rheumatology.
CRIS-Team Scopus Importer:2021-10-15
Keywords: Crowd sourcing; Digitalization; Ehealth; Health services research; Tools